Soil test crop response based phosphorous calibration study on maize at Abay Choman district, Horo Guduru Wollega zone, Oromia region, Ethiopia - Chimdessa, Temesgen; Takele, Chalsissa; Bayeta, Garamu; Gemada, Firaol; Leta, Rafisa (Journal of Scientific Agriculture, 2023)
Soil test crop response-based P calibration study can give farmers more economic use of fertilizers and better soil management practices. In a view of this, the trial was done in the Abay Choman district on ten experimental farmers’ fields in the first year of the experiment (2018/19 cropping season) to determine the economic rate of N and on twenty farmers’ fields in the second and third years of the experiment (2019/20 and 2020/21 cropping season respectively) to determine phosphorus critical level and requirement factor. In the first year of the experiment, the treatments were combined in factorial with four levels of phosphorus (0, 10, 20, 40 kg/ha) and four levels of nitrogen (0, 46, 92 and 138 kg/ha). While experiments in the second and third years of the experiment were six levels of Phosphorus 0, 10, 20, 30, 40 and 50 kg/ha. The treatments were laid out as a randomized complete block design (RCBD) with three replications. Representative soil samples were taken before planting and analyzed. Experimental sites that have a pH of < 5.5 were amended using the lime application before the setup of the experiment. Soil test results of the study sites before planting indicated that pH values of most soils were strongly acidic (<5.5) and available phosphorus of experimental soil ranged from 3.22 to 13.62 pp. The main effects of both N and P significantly influenced the mean grain yield of maize, but their interaction was not significant with a grand mean of 76.53 qt/ha during the N determination trial. Economic analysis using partial budget analysis showed 92 kg/ha of N was economically optimal for the production of maize in the Abay Choman district. The study also showed that P- the critical value (12 ppm) and P- the requirement factor (10.55 Kg P/ha) were determined for the phosphorus fertilizer recommendation in the study area. Thus, the farmers in the area might be advised to use soil test crop response-based fertilizer recommendations to increase the productivity of maize in and around the study district.